(untitled) (Doctor Virtualis, 2023)
This essay means to put the spotlight on the role that analogy played in medieval jurists’ modus operandi and modus arguendi, suggesting a multi-level reading of it as well, from the point of view of Il paradigma filosofico agostiniano (Parodi 2006).